A collocated finite volume method for incompressible flow on unstructured meshes. (6th April 2005) - Yu, Bo; Ozoe, Hiroyuki; Tao, Wen-Quan
A finite volume method on unstructured meshes for the solution of incompressible Navier-Stokes equations is presented in this paper. New second-order spatial discretisations for convection and diffusion terms are developed. A non-staggered variable arrangement was utilised for all variables. Momentum interpolation technique was employed to avoid pressure checker boarding. To minimise storage requirement, a segregated solution strategy was adopted with pressure and velocity coupled by the SIMPLE method. The proposed finite volume scheme was applied to several standard problems. Computational results show that the performance of the scheme is satisfactory.